A Novel CAR Expressing NK Cell Targeting CD25 With the Prospect of Overcoming Immune Escape Mechanism in Cancers - Dehbashi, Moein; Hojati, Zohreh; Motovali-bashi, Majid; Ganjalikhany, Mohamad Reza; Cho, William C.; Shimosaka, Akihiro; Navabi, Parnian; Ganjalikhani-Hakemi, Mazdak (Frontiers in Oncology, 2021)
For many years, high-affinity subunit of IL-2 receptor (CD25) has been considered as a promising therapeutic target for different pathologic conditions like allograft rejection, autoimmunity, and cancers. Although CD25 is transiently expressed by newly-activated T cells, it is the hallmark of regulatory T (Treg) cells which are the most important immunosuppressive elements in tumor microenvironment (TME). Thus, Tregs can be considered as a potential target for chimeric antigen receptor (CAR)-based therapeutic approaches. On the other hand, due to some profound adverse effects pertaining to the use of CAR T cells, CAR NK cells have caught researchers’ attention as a safer choice. Based on these, the aim of this study was to design and develop a CAR NK cell against CD25 as the most prominent biomarker of Tregs with the prospect of overcoming immune escape mechanism in solid and liquid cancers. In the current study, an anti-CD25 CAR was designed and evaluated by comprehensive in silico analyses. Then, using lentiviral transduction system, NK-92 cell line was engineered to express this anti-CD25 CAR construct. In vitro functional analyses of anti-CD25 CAR for its reactivity against CD25 antigen as well as for cytotoxicity and cytokine production assays against CD25 bearing Jurkat cell line were done. In silico analyses demonstrated that the anti-CD25 CAR transcript and scFv protein structures were stable and had proper interaction with the target. Also, in vitro analyses showed that the anti-CD25 chimeric antigen receptor-engineered NK-92 cells were able to specifically detect and lyse target cells with an appropriate cytokine production and cytotoxic activity. To conclude, the results showed that this novel CAR NK cell is functional and warrant for further investigations.